MAJOR RISK FACTORS OF THE DISEASE IN THE FOCI OF DRUG-RESISTANT TUBERCULOSIS - T. Sh. Abildaev; G. S. Bekembaeva; L. Z. Kastykpaeva (Туберкулез и болезни лёгких)
The paper analyzes contamination factors in children and adolescents from the foci of multidrug-resistant tuberculosis. The analysis of a study of these disease sources, the people who discontinued treatment and contacted with the children and adolescents in the foci demonstrated that these were mainly male alcoholics, as well as unemployed, intensive-phase therapy non-compliant inpatients, patients who went home without permission; 16% of them had convictions. The contacted children and adolescents from a group of patients who discontinued treatment were significantly more frequently stated to have a hyperergic response to tuberculin (10.8%) than those who continued treatment (3.4%) (p ≤ 0.05). Two children and 3 adolescents (15%) fell ill in the treatment discontinuation group. One (3.0%) adolescent did in the treatment continuation group (p ≤ 0.05).